Predicting perceived sport performance via self-determination theory - Lourenço, J.; Almagro, B. J.; Carmona-Márquez, J.; Sáenz-López, P. (Perceptual and Motor Skills, 2022)
Sport performance depends in part on psychological factors. Self-determination theory emphasizes that the satisfisfaction of basic psychological needs and autonomous motivation may be linked to positive behavioral results and positive perceptions of performance. Our main objective in this study was to analyze the predictive power of such variables as perceived autonomy support, the satisfaction of psychological needs, and autonomous motivation on perceived sport performance. We recruited 447 young Portuguese athletes/participants (340 males, 107 females; Mage = 15.72 years, SD = 1.8). We had participants complete Portuguese sport versions of the Perceived Autonomy Support Exercise Climate Questionnaire, the Basic Psychological Needs in Exercise Scale, the Behavior Regulation Sport Questionnaire and the Perceived Performance in Sport Questionnaire. A gender invariant structural equation model showed that the coach`s autonomy support significantly predicted the satisfaction of psychological needs for autonomy, competence, and relatedness. The satisfaction of these three psychological needs predicted autonomous motivation. Satisfying the need for competence positively predicted perceived sport performance, but autonomous motivation was not significantly related to perceived performance.